An introduction to zwitterionic polymer behavior and applications in solution and at surfaces. (14th December 2018) - Blackman, Lewis D.; Gunatillake, Pathiraja A.; Cass, Peter; Locock, Katherine E. S.
Abstract : Zwitterionic polymers, including polyampholytes and polybetaines, are polymers with both positive and negative charges incorporated into their structure. Abstract : Zwitterionic polymers, including polyampholytes and polybetaines, are polymers with both positive and negative charges incorporated into their structure. They are a unique class of smart materials with great potential in a broad range of applications in nanotechnology, biomaterials science, nanomedicine and healthcare, as additives for bulk construction materials and crude oil, and in water remediation. In this Tutorial Review, we aim to highlight their structural diversity and design criteria, and their preparation using modern techniques. Their behavior, both in solution and at surfaces, will be examined under a range of environmental conditions. Finally, we will exemplify how their unique behaviors give rise to specific properties tailored to a selection of their numerous applications.